Numerical Study of the Effect of Water on the Flow Behaviour of Landslide-Generated Debris - Ray A.; Rai R.; Singh T.N. (My University, 2025)
Landslide-generated debris flow is one of the severe outcomes of slope failure in hilly areas that have the potential to severely affect the physical and biological environment. The precise identification of the vulnerable areas depends on a broad understanding of the flow morphology and deposition process of the flowing debris. However, owing to varying compositions of the flowing debris coupled with inherent complex field topography, makes the flow prediction more complex. In this study, numerical analysis was performed using a distinct element-based numerical modelling technique. The numerical model was calibrated using a physical scale-down model of the residual soil slope. Calibration of the numerical model was performed under both dry and wet debris flow induced in the scale-down laboratory model. The final calibrated model was used to validate a case study. Following the successful validation of the developed numerical model, parametric analysis (various slope profiles, heights, inclinations, and particle size distributions of debris) was performed to study the rheology of the debris under both dry and wet conditions generated post-landslide event. This study gives a reliable idea about the possible flow behaviour in a simple residual soil slope and can be used as a guide to performing debris flow analysis for any natural slope. It also emphasises the need for the adoption of more robust debris runoff preventive measures in case of failures observed after precipitation owing to the very high energy and momentum of flowing wet debris in comparison with dry debris. © The Author(s), under exclusive licence to Indian Geotechnical Society 2023.